Pregnancy Associated Cancer in Yemen: An Observational Study - Al Harazi, Abdelrahman Hasan; Mehrass, Amat Al-Khaleq O. (Annals of Medicine & Health, 2023)
Background: Cancer in pregnancy is not uncommon and represents a complex problem requiring consideration for both the mother and fetus.Aim: The objective of this study is to analyze the frequency, the clinical feature of cancer diagnosed during pregnancy and the obstetric outcomes. Methods: This is a single-center, retrospective analysis of women who were diagnosed with cancer during pregnancy at Saudi Hospital Hajjah (SHH) between Jan 2016 and Dec 2017. Maternal sociodemographic, and obstetrical data including age, parity, gestational age at diagnosis, type, stage, symptoms and signs of cancer for each patient were retrieved from the hospital database.Results: Among 32400 pregnant women seen in antenatal care clinic, there were 17 women diagnosed with cancer. The mean age of women was 33.94 ± 4.80 years, the mean gestational age was 26.88 ± 7.5 weeks and the mean parity was 4.0 ± 2. The most frequent cancer found was ovarian cancer (23.5%), gastrointestinal cancer (23.5%) and cervical cancer (17.6%). Stage II was the most frequently found in 9 women (52.9%). Therapeutic abortion was performed for 9 cases (52.9%) and induced preterm labor for 8 cases (47.0%). Among those induced birth, 6 fetuses were liveborn and 2 deaths. (25.0%). All patients were referred to specialized centers after delivery.Conclusion: Based on these results, the incidence of cancer complicated pregnancy was 0.052 % (52.4/100000 pregnancies). Gynecological cancer such as ovarian, cervical and breast are more frequent and the gestational age at diagnosis is the most important factor both for the choosing the appropriate obstetrical management and also for the mother prognosis